Advanced Prompting Techniques for Artificial Intelligence-Based Learning Innovation - Budiman, Adam Arif; Setiawan, Aji; Yudha, Afri; Supriatna, Ade; Kurnianto, Ario; Sofyan Andhana Saputra, Yan; Dariyus, Asyari (JEPTIRA, 2025)
This community service program was designed to strengthen the capacity of teachers and lecturers in utilizing advanced prompting techniques based on Artificial Intelligence (AI) to support instructional innovation. The focus of the training was on two effective methods Chain of Thought (CoT) and Role Prompting which enhance human-AI interaction in educational contexts. The activity was conducted through face-to-face workshops involving 25 participants from various educational institutions, combining theoretical explanations, hands-on practice, and case-based discussions. Participants learned how to construct structured and contextual prompts for teaching applications such as lesson planning, explanation of concepts, and simulation-based learning. Evaluation results showed a significant improvement in participants’ understanding and ability to apply prompt engineering strategies, as reflected in both assessment scores and the quality of practical outputs. The program also contributed to raising awareness about ethical AI usage in education and emphasized the role of digital literacy in enabling educators to adapt to the demands of digital transformation.